Iron man: armor wars ebook - Caramagna, Joe (Iron Man (1968)., 2017)
Collects Iron Man & The Armor Wars #1-4, Iron Man #225. Cash, cars, boats, houses...Tony Stark has got it all. The only thing that could ruin his day? If every single one of his IRON MAN armors were stolen, and then turned against him. Join us for a nail-biting, strapped-to-your-seat adventure as Tony battles his greatest creations, and tries to discover who could (gasp) OUTSMART him!?!?